2008
DOI: 10.1088/1475-7516/2008/04/036
|View full text |Cite
|
Sign up to set email alerts
|

Preheating in derivatively coupled inflation models

Abstract: We study preheating in theories where the inflaton couples derivatively to scalar and gauge fields. Such couplings may dominate in natural models of inflation, in which the flatness of the inflaton potential is related to an approximate shift symmetry of the inflaton. We compare our results with previously studied models with non-derivative couplings. For sufficiently heavy scalar matter, parametric resonance is ineffective in reheating the universe, because the couplings of the inflaton to matter are very wea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 38 publications
2
40
2
Order By: Relevance
“…Ref. [30]. Our model has long been proposed as a mechanism for generating primordial magnetic fields.…”
Section: Introductionmentioning
confidence: 93%
“…Ref. [30]. Our model has long been proposed as a mechanism for generating primordial magnetic fields.…”
Section: Introductionmentioning
confidence: 93%
“…Our approach captures this model by now choosing α 3 = 2φ 0 (t) 2 /Λ 2 . It has been found that preheating in models that preserve an inflaton shift symmetry is not efficient [22]. One reason for this is that naively we assume that the energy of the fields can not exceed the cutoff Λ.…”
Section: Reheating Fields and Coupling To The Inflatonmentioning
confidence: 99%
“…Instead of equations (31) and (39), which are valid only in the limit of small ǫ, we use the general equations (18) with L i taken as the numerical value of the band widths for each model. In Figure 2 a), we see that the e-fold time is essentially determined by the contribution of the first instability band, except in the region of very small values of ǫ.…”
Section: Reheating Efficiency Of the Two Couplingsmentioning
confidence: 99%
“…Since, however, only the contribution of the first instability band is accounted for in the efficiency estimates found in the literature, these estimates remain valid for the multi-frequency model. Now equations (31) and (39) are valid as long as any given mode remains in the resonance band. Due to the expansion, the time interval ∆τ during which a mode remains in the band is ∆τ ≃ L Hm 2 .…”
Section: Reheating Efficiency In the Expanding Universementioning
confidence: 99%
See 1 more Smart Citation